Cyclic deformation behavior of modified 9Cr–1Mo steel at elevated temperatures - Singh V.; Verma P. (My University, 2025)
Modified 9Cr–1Mo steel exhibited dynamic strain ageing (DSA) in the temperature range from 523 to 673 K and it was established on the basis of plateau/peak in yield and tensile strength, minima in ductility and serrations in stress–strain curve. High density of dislocations and typical features like dislocation debris, kinks and bowing of dislocations was observed in the regime of DSA. This steel exhibited cyclic softening irrespective of the strain amplitude, strain rate, and temperature. The observed cyclic softening is associated with many factors like cell formation at room temperature and additionally annihilation of array of dislocations at 573 K, in addition to coarsening of carbides at 873 K. © The Minerals, Metals & Materials Society 2017.